Genetic Diversity and Characteristics of Drug Resistance Among Treatment-Naive People Living with HIV in Xi’an, China - Xia H; Jin J; Ba H; Zhang Y; Li J; Guo R; Li Y; Ma P; Zhang Y (Dove Medical Press, 2023)
Huan Xia,1,2,* Juan Jin,3,* Huanhuan Ba,3 Yuan Zhang,3 Jiajia Li,3 Rui Guo,3 Ying Li,3 Ping Ma,1,2 Yan Zhang3 1Department of Infectious Diseases, Tianjin Second People's Hospital, Tianjin, 300192, People's Republic of China; 2Tianjin Association of STD/AIDS Prevention and Control, Tianjin, 300011, People's Republic of China; 3Department of Infectious Diseases, Xi'an Eighth's Hospital, Xi'an, Shaanxi, 710061, People's Republic of China*These authors contributed equally to this workCorrespondence: Yan Zhang, Xi'an Eighth's Hospital, 2 Zhangba East Road, Yanta District, Xi'an, Shaanxi, 710061, People's Republic of China, Tel/Fax +86-29-85393973, Email 1522649620@qq.com Ping Ma, Tianjin Second People's Hospital, 7 Sudi South Road, Nankai District, Tianjin, Tianjin, 300192, People's Republic of China, Tel/Fax +86-22-27468129, Email mapingtianjin@163.comPurpose: The genetic diversity and genetic predisposition for drug resistance mutations are the primary features of human immunodeficiency virus type 1 (HIV-1), which could cause the incidence of failure of antiretroviral therapy (ART). This study investigates the distribution of various HIV-1 genotypes and the incidence of pretreatment drug resistance (PDR) in the antiretroviral-naive HIV-1 infected participants in Xi'an, China.Patients and Methods: In this study, a cross-sectional analysis was carried out at the Xi'an Eighth Hospital between January 2020 and December 2021 among newly-diagnosed ART-naive HIV-1 infected participants. A nested PCR technique was used for amplifying the target segment of 1.3 kb present in the pol gene that spanned the reverse transcriptase and the protease regions. HIV-1 genotypes and the PDR-associated mutations were identified using the Stanford HIV Drug Resistance Database.Results: A total of 317 pol gene sequences were retrieved, amplified, and sequenced. The circulating recombinant form (CRF), CRF07_BC (51.7%) was seen to be the most prevalent HIV-1 genotype, followed by other genotypes like CRF01_AE (25.9%), B (14.2%), and CRF55_01B (4.7%). PDR was found in 18.3% of the population. The PDR mutation frequency in the non-nucleoside reverse transcriptase inhibitor (NNRTI) (16.1%) was significantly higher compared to that of the nucleoside reverse transcriptase inhibitor (NRTI) (4.4%) and the protease inhibitor (0.9%). V179D/E (both were 4.4%) was seen to be the most predominant type of NNRTI mutation. K65R and M184V (1.3%) were the most frequent NRTI-associated mutations. About half (48.3%) of the sequenced HIV-1 strains that had mutations could show a potential low-level NNRTI resistance owing to V179D/E. Multivariate regression analysis revealed one PDR mutation associated with subtype CRF01_AE (p=0.002) and CRF55_01B (p< 0.001) as a higher risk mutation.Conclusion: Diverse and complex HIV-1 genotypes are distributed in Xi'an, China. Considering new evidence, it is necessary to screen for baseline HIV-1 drug resistance among the newly-diagnosed HIV-1 individuals.Keywords: human immunodeficiency virus, drug resistance, pre-treatment, China